Minorities within minorities: equality, rights, and diversity - Eisenberg, Avigail (Cambridge Univ. Press, 2005)
Most discussions of multiculturalism and group rights focus on the relationship between the minority and the majority. This volume advances our understanding of minority rights by focusing on conflicts that arise within minority groups and by examining the different sorts of responses that the liberal state might have to these conflicts. Groups around the world are increasingly successful in maintaining or winning autonomy. In light of this trend, a crucial question emerges: what happens to individuals within groups who find that their group discriminates against them? This volume brings together distinguished scholars who examine this question by weaving together normative political theory with case studies drawn from South Africa, the United States, India, Canada, and Britain. Classical liberalism, deliberative democracy, feminism, and associative democracy are among the theoretical frameworks used to offer solutions to the complex set of issues raised by minorities within minorities.